Defective mitochondrial function in vivo in skeletal muscle in adults with Down's syndrome: a 31P-MRS study. - Alexander C Phillips; Alison Sleigh; Catherine J McAllister; Soren Brage; T Adrian Carpenter; Graham J Kemp; Anthony J Holland (PLoS ONE)
Down's syndrome (DS) is a developmental disorder associated with intellectual disability (ID). We have previously shown that people with DS engage in very low levels of exercise compared to people with ID not due to DS. Many aspects of the DS phenotype, such as dementia, low activity levels and poor muscle tone, are shared with disorders of mitochondrial origin, and mitochondrial dysfunction has been demonstrated in cultured DS tissue. We undertook a phosphorus magnetic resonance spectroscopy ((31)P-MRS) study in the quadriceps muscle of 14 people with DS and 11 non-DS ID controls to investigate the post-exercise resynthesis kinetics of phosphocreatine (PCr), which relies on mitochondrial respiratory function and yields a measure of muscle mitochondrial function in vivo. We found that the PCr recovery rate constant was significantly decreased in adults with DS compared to non-DS ID controls (1.7 ± 0.1 min(-1) vs 2.1 ± 0.1 min(-1) respectively) who were matched for physical activity levels, indicating that muscle mitochondrial function in vivo is impaired in DS. This is the first study to investigate mitochondrial function in vivo in DS using (31)P-MRS. Our study is consistent with previous in vitro studies, supporting a theory of a global mitochondrial defect in DS.